2014
DOI: 10.2478/s13382-014-0285-5
|View full text |Cite
|
Sign up to set email alerts
|

Global review of studies on traffic police with special focus on environmental health effects

Abstract: Since occupation is a major determinant of health, traffic police personnel face multiple occupational hazards. They are continuously exposed to vehicular emissions and work in a noisy and polluted environment. The objective of the present review is to explore the impact of occupational health hazards on the health of traffic police personnel. Published research papers on traffic police reporting occupational health issues were accessed and reviewed. Attempts were made to access papers that reported negative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 71 publications
(48 reference statements)
0
20
0
1
Order By: Relevance
“…1 Likewise the study done by Patel et al (2014) on "Global review of studies on Traffi c police with special focus on Environmental Health Eff ects" showed correlation between atmospheric pollution and some possible outcomes like ergonomic impact, damaged oral health, hearing loss, traffi c injuries, personal protective equipments (PPEs), reproductive eff ects in traffi c policemen wives, and vascular infl ammatory reactions in traffi c policemen. 36 Burton et al in 1996 revealed that physical stress as one of the occupational risk factors for low LBP among police offi cers managing traffi c which often leading to increased sickness absenteeism. 37 So, stress can be responsible for a number of physical symptoms, including muscle tension and back pain.…”
Section: Discussionmentioning
confidence: 99%
“…1 Likewise the study done by Patel et al (2014) on "Global review of studies on Traffi c police with special focus on Environmental Health Eff ects" showed correlation between atmospheric pollution and some possible outcomes like ergonomic impact, damaged oral health, hearing loss, traffi c injuries, personal protective equipments (PPEs), reproductive eff ects in traffi c policemen wives, and vascular infl ammatory reactions in traffi c policemen. 36 Burton et al in 1996 revealed that physical stress as one of the occupational risk factors for low LBP among police offi cers managing traffi c which often leading to increased sickness absenteeism. 37 So, stress can be responsible for a number of physical symptoms, including muscle tension and back pain.…”
Section: Discussionmentioning
confidence: 99%
“…On contrast, the effect of environmental lead pollution and high blood lead level has not always yielded convincing positive results. Many studies have failed to detect increased blood lead levels among traffic police, even when the subjects were tested with a sophisticated electro-thermal atomic absorption spectrometer [28] . In our own opinion, the safety limit that was set for the maximum blood lead levels is not restrict and still controversial issue, Manser, et al [21] , reported that the upper limits for blood lead levels has been often quoted as 40 μg/dl for adults and 30 μg/dl for children, while 25 μg/dl blood lead regarded as elevated in U.S.A as adopted by CDC [6] , and the European Committee decided on a mean acceptable value of 20 μg/dl [9] .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in this study, our aim was to identify the common health problems and the factors associated with general anxiety among the tra c police working in Kathmandu and Lalitpur. We believe, this sort of occupational health studies would help us to understand occupational circumstances and their adverse in uence on health and wellbeing of tra c police [11].…”
Section: Introductionmentioning
confidence: 98%
“…In addition, tra c police are highly stressed due to their nature of work, work conditions and work surroundings, and a number of these occupational factors could attribute to general anxiety among tra c police [11]. There have no studies documented yet explaining health problems including general anxiety among Nepalese tra c police.…”
Section: Introductionmentioning
confidence: 99%